Sejarah dan Sistem Pendidikan di Turki - Harisma Juliani; Mislaini Mislaini; Aisyah Qurotul Sabila (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study discusses the history and education system in Turkey, focusing on the developments and challenges faced. Turkey, as a country located in the Eurasian region, has a centralized education system and is managed according to the provisions set by Mustafa Kamal Ataturk. The purpose of this education system is to produce skilled, productive, and creative individuals in the era of reform. Some important points raised in this study include: Quality of Education, although there are many quality higher education institutions, the global ranking of the Turkish education system still needs to be improved. Improving the quality of teaching and curriculum development are key to facing this challenge. Educational Inequality, there is inequality in access to education, especially in rural areas. Although basic education is mandatory, there are still areas in Turkey that experience limited access to education, which creates a gap between urban and rural areas. Educational Reform, since 2012, the structure of education in Turkey has changed, where students must complete upper secondary education which is now mandatory. Previously, students completed basic education for eight years and secondary education for three years. Comparison with Indonesia, the education system in Turkey has similarities with Indonesia, especially in the use of a modern system in implementing the curriculum in universities. However, Turkey has greater academic autonomy in universities. Investment in Education, Turkey has invested in education through the "2023 Eğitim Vizyonu" program to improve the quality and accessibility of education. However, challenges such as educational inequality still need to be addressed. This study is expected to provide deeper insight into the education system in Turkey and the challenges faced, as well as comparisons with education systems in other countries, especially Indonesia.